Earnings Management in Indonesian Islamic Banking: Analyzing with Modified Jones Model - Supatminingsih, Tuti; Rijal, Syamsu (Al Urwah : Sharia Economics Journal, 2023)
Company management follows earnings management to influence the earnings reported in the financial statements. This study aims to analyze whether there are earnings management activities in Islamic banking in Indonesia. The data taken for this study are the financial reports of Islamic Commercial Banks registered with the Financial Services Authority (OJK) for 2017-2021. Earnings management is measured by the discretionary accrual method using the Modified Jones Model. This research shows that the discretionary accruals (DAC) for Islamic Commercial Banks in 2017-2021 have a minimum result of -1.3614 and a maximum result of 0.2917. This shows that there have been earnings management activities in Islamic Commercial Banks in the last 5 years. To reduce earnings management, the Sharia Supervisory Board (DPS) is asked to be truly qualified in carrying out its duties so that profit management of Islamic bank financial reports can be reduced, readers of financial reports are not deceived, and investors are not harmed.